Analysis and Visualization of Social Data - Garg, Puneet (My University, 2015)
Social media has become very popular communication tool among internet users in the recent years. Humans have an ingrained tendency to share their ideas, experiences and knowledge, which associate them with the rest of the world, so that they can be recognized and can also identify their importance and worth. They are eager to know about happenings around them, that is why they communicate in order to share their ideas, observations and queries. Social media is one such communication medium that made people to be heard and satisfy their curiosity to know about rest of the world. A large unstructured data is available for analysis on the social web. The data available on these sites have redundancies as users are free to enter the data according to their knowledge and interest. This data needs to be normalized before doing any analysis due to the presence of various redundancies in it. Analyzing these huge social datasets and predicting the opinions of individuals plays an important role in business and academics. In this research, LinkedIn data is extracted by using LinkedIn API and normalized by removing redundancies. Further, data is also normalized according to locations of LinkedIn connections using geo coordinates provided by Microsoft Bing. Then, clustering of this normalized data set is done according to job title, company names and geographic locations using Greedy, Hierarchical and K-Means clustering algorithms and clusters are visualized to have a better insight into them. Secondly, we extract tweets about “AAM AADMI PARTY” (a recently grown political party) and build a development environment using python to induce analytical insights from these tweets using frequency analysis and sentiment analysis.
ME, CSED
Keywords: Twitter APIs, Social Data Analysis, Python, Clustering; CSED